Oral antibiotics are as effective as intravenous antibiotics for postdischarge treatment of complicated pneumonia in children. - Onakpoya, I (BMJ Publishing Group, 2017)
In children, complicated pneumonia implies pneumonia infection that is associated with pleural effusion or empyema. The initial management involves use of parenteral broad spectrum antibiotics to cover the most common organisms; thoracotomy or chest tube insertion may be indicated if there is no response to antibiotic therapy, or if there is significant respiratory difficulty. Most national guidelines do not specify the preferred route of antibiotic therapy for post-discharge treatment of complicated pneumonia in children, and the guidance are mostly based on historical precedence. For instance, British guidelines recommend a switch to oral antibiotics if there is clear evidence of improvement, while American guidelines are non-specific. This retrospective study compared the benefits and harms of intravenous versus oral antibiotic therapy for treatment of complicated pneumonia in children post-discharge.